Grootboom: A paradigm of individual remedies versus reasonable programmes - Mbazira, Christopher (Southern African Public Law, 2023)
The decision of the Constitutional Court (the Court) in the case of Government of the Republic of South Africa versus Grootboom was received as ground breaking by human rights practitioners, scholars and advocates the world over. If it were possible to assess the case in terms of new music releases, one would say that the ‘Grootboom album’ became an instant hit on the top of all music charts. The case instantly established itself as a landmark, signifying the undeniable justiciability of economic and social rights (socio-economic rights).